THE LANGUAGE OF THE GAME : How to Understand Soccer - Dubois, Laurent, 1971- (New York : Basic Books, 2018)
"A passionate and engaging introduction to soccer's history, tactics, and human drama. Profiling soccer's full cast of characters--goalies and position players, referees and managers, commentators and fans--historian and soccer scholar Laurent Dubois describes how the game's low scores, relentless motion, and spectacular individual performances combine to turn each match into a unique and unpredictable story. He also shows how soccer's global reach makes it an unparalleled theater for nationalism, international conflict, and human interconnectedness"--Amazon.com.
Introduction -- The Goalkeeper -- The Defender -- The Midfielder -- The Forward -- The Manager -- The Referee -- The Fan.
Includes index.
Bibliography: pages 227-291.
Keywords: Soccer; Soccer -- Handbooks, manuals, etc